Comparison between the outcome of proximal femoral locking compression plate and dynamic hip screw in intertrochanteric femoral fractures - Arif, Adnan; Bhatti, Hamza Waqar; Chaudhary, Noman Ahmed; Sadiq, Abdullah (International Surgery Journal, 2021)
Background: Inter-trochanteric femoral fractures are associated with a high complication rate and mortality. This study aims to compare the proximal femoral locking compression plate (PFLCP) with dynamic hip screws (DHS) for inter-trochanteric femoral fractures in terms of mean bone union time. Methods: It was a prospective randomized study conducted at the department of orthopedics, Benazir Bhutto Hospital, Rawalpindi, Pakistan from June 2015 to December 2015. Sixty patients with a diagnosis of inter-trochanteric fractures, requiring orthopedic surgery, were included in the study. After randomization thirty patients underwent PFLCP fixation and the other thirty patients underwent DHS fixation. Patient information, demographic data, and functional level were assessed. Mean bone union time and implant complications were compared for the two treatment groups. Results: Patients who underwent PFLCP fixation demonstrated shorter bone union time (2.8±0.2 months) than those who underwent DHS fixation (3.2±0.1 months) (p<0.000). PFLCP group had 90% bone union whereas DHS group had 76.66% bone union at 12 weeks (p=0.16). Conclusions: PFLCP is better than DHS for intertrochanteric femoral fractures in terms of shorter mean bone union time and fewer complications.